A case study on evaluation of the context, input, process, product (CIPP) implementation in the child-friendly school program - Barella, Yusawinur; Ginting, Daniel; Nur Akbar Rasyid, Muhammad; Mania, Sitti (Edelweiss Applied Science and Technology, 2024)
This study evaluates the effectiveness of the Child-Friendly School (CFS) program at Al Mumtaz Integrated Islamic Elementary School in Pontianak using the CIPP (Context, Input, Process, Product) Evaluation Model. Through field research and purposive sampling, it delves the experiences and perceptions of principals, vice-principals, students, teachers, and parents on the program’s impact. The school has successfully implemented the CFS program, noted for its qualified teachers with professional educational backgrounds and a focus on religious knowledge. The context evaluation revealed that the program aligns with child-friendly school policies, receiving a very positive evaluation and documented by official decrees. Input evaluation indicates Al Mumtaz meets all criteria including qualified staff, infrastructure, educator training, and engagement from students and parents. Process evaluation highlights the school’s effectiveness in facilitating positive educational dynamics, with non-violent disciplining, affection towards students, democratic educational practices, and teachers as role models. Finally, product evaluation shows significant achievements in fostering students’ holistic development across various dimensions such as honesty, tolerance, communicative skills, democracy, social concern, responsibility, environmental care, and academics. The suggestion for this school involves establishing an organizational framework within the child-friendly school initiative to facilitate the efficient allocation of responsibilities and to confirm that the program’s monitoring and evaluation procedures are conducted in a more organized and methodical manner.